Principles of meiotic chromosome assembly revealed in S. cerevisiae - Stephanie A. Schalbetter (Nature Portfolio, 2019)
During meiotic prophase chromosomes organise into a series of chromatin loops, but the mechanisms of assembly remain unclear. Here the authors use Saccharomyces cerevisiae to elucidate how this elaborate three-dimensional chromosome organisation is linked to genomic sequence, and demonstrate an essential role for cohesin during this process.